The list of phone numbers and the paradox of representation. Reflections on resilience in a cross-border contex - Ocskay, Gyula (Észak-magyarországi Stratégiai Füzetek, 2023)
The COVID-19 pandemic has generated unharmonised measures on behalf of the national governments without communicating with the local actors of the border areas, the representatives of the existing cross-border structures included. Against the conclusions of several studies discussing the topic, the author claims that, notwithstanding a few exceptions, the cross-border structures established so far all over Europe were not involved in the management of the extreme situation. Instead, these were the interpersonal contacts of border citizens and informal channels through which derogations of strict measures were achieved at the regional and national governments. The author finds the reason of this phenomenon in the ‘paradox of representation’ meaning the controversial procedure through which border areas gradually obtain the legal entity status but they lose their societal basis. To illustrate this procedure, the study refers to three communities of experts of network governance, and, through their theoretical models, it arguments that in parallel with the institutionalisation of crossborder cooperation, its participative aspects gradually weaken. The COVID-19 pandemic clearly showed in practice, how this process stabilised the territorial representation status of the cross-border structures while it emptied the participative platforms of the citizens therein.